Drinking-Straw Microbalance and Seesaw: Stability and Instability - Chapman, P.; Glasser, Leslie (AMER ASSN PHYSICS TEACHERS, 2015)
The mechanics of a beam balance are little appreciated and seldom understood. We here consider the conditions that result in a stable balance, with center of gravity below the fulcrum (pivot point), while an unstable balance results when the center of gravity is above the fulcrum. The highly sensitive drinking-straw microbalance, which uses a plastic drinking straw as a rigid beam, is briefly described with some slight convenient modifications. Different placements of the center of gravity are considered analytically to explain the equilibrium neutrality, stability, and instability of such beam balances as the microbalance, the playground “seesaw” or “teeter-totter,” the “dipping bird,” and other toys and magic tricks.